∫ 0 π e x sin 2 ( x ) d x
The above integral has a simple exact closed form. Evaluate this integral and give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
certainly easy solution took me long to solve this, how fast do you solve the problem and how do you realize to use certain things instead others?
Log in to reply
I like to use e i θ = cos θ + i sin θ . Frequently, it simplifies matter. In this case integration of e z is simple.
Exponential + trig combination functions always scream to me to use Euler's Cosine & Sine Identities as a simple substitution (much like Chew-Seong's hint above). That helps transform the above integrand into a series of exponential function terms that is readily integrable.
Log in to reply
yes sir i am also learning to be aware when yo use Euler cosines and sin identities.
Yes, Euler is my greatest mathematician.
Great solution !
To do this problem the way I did, we first find the antiderivative of e x sin 2 ( x ) and then using the fundamental theorem of calculus, solve this problem. Firstly though, we use integration by parts a few times ∫ e x sin 2 ( x ) d x ⟹ 5 ∫ e x sin 2 ( x ) d x ⟹ ∫ e x sin 2 ( x ) d x = e x sin 2 ( x ) − ( ∫ e x ( 2 sin ( x ) cos ( x ) ) d x ) = e x sin 2 ( x ) − 2 ∫ e x sin ( x ) cos ( x ) d x = e x sin 2 ( x ) − 2 ( e x sin ( x ) cos ( x ) − ∫ e x ( cos 2 ( x ) − sin 2 ( x ) ) d x ) = e x sin 2 ( x ) − 2 e x sin ( x ) cos ( x ) + 2 ∫ e x ( 1 − 2 sin 2 ( x ) ) d x = e x sin 2 ( x ) − 2 e x sin ( x ) cos ( x ) + 2 e x − 4 ∫ e x sin 2 ( x ) d x = e x sin 2 ( x ) − 2 e x sin ( x ) cos ( x ) + 2 e x = 5 1 ( e x sin 2 ( x ) − 2 e x sin ( x ) cos ( x ) + 2 e x )
Let F ( x ) = 5 1 ( e x sin 2 ( x ) − 2 e x sin ( x ) cos ( x ) + 2 e x ) . By direct calculation (and realising that sin ( 0 ) = sin ( π ) = 0 ), we have F ( 0 ) = 5 2 and F ( π ) = 5 2 e π . And hence we have our final answer. ∫ 0 π e x sin 2 ( x ) d x = F ( π ) − F ( 0 ) = 5 2 ( e π − 1 ) Which rounds to 8 . 8 5 6
i did the same old boring thing
I got the answer, but it took like two pages of work with trig identities and IBP, was there something I missed?
Try to solve it using complex numbers. Do refer to Chew-Seong Cheong's solution.
Problem Loading...
Note Loading...
Set Loading...
∫ 0 π e x sin 2 x d x = 2 1 ∫ 0 π e x ( 1 − cos ( 2 x ) ) d x = 2 1 ∫ 0 π e x d x − 4 1 ∫ 0 π e x ( e 2 x i + e − 2 x i ) d x = 2 1 [ e x ] 0 π − 4 1 [ 1 + 2 i e ( 1 + 2 i ) x + 1 − 2 i e ( 1 − 2 i ) x ] 0 π = 2 1 ( e π − 1 ) − 4 1 [ 1 + 4 e x ( e 2 x i + e − 2 x i − 2 i e 2 x i + 2 i e − 2 x i ) ] 0 π = 2 1 ( e π − 1 ) − 2 1 [ 5 e x ( cos ( 2 x ) + 2 i sin ( 2 x ) ) ] 0 π = 2 1 ( e π − 1 ) − 1 0 1 [ e π ( cos ( 2 π ) + 2 i sin ( 2 π ) ) − e 0 ( cos 0 + 2 i sin 0 ) ] = 2 1 ( e π − 1 ) − 1 0 1 ( e π − 1 ) = 5 2 ( e π − 1 ) = 8 . 8 5 6